2023
DOI: 10.3389/fmicb.2022.1103998
|View full text |Cite
|
Sign up to set email alerts
|

Microbial metabolites indole derivatives sensitize mice to D-GalN/LPS induced-acute liver failure via the Tlr2/NF-κB pathway

Abstract: IntroductionAcute liver failure (ALF) is a clinical condition with many causes, fast progression, and a poor prognosis. Previous research has indicated that microbial factors have a role in ALF, but a clear picture has yet to emerge.MethodsTo investigate the specific involvement of microbial metabolites in ALF development, we pretreated D-GalN/LPS-induced ALF mice with indole derivatives, an influential class of gut microbial metabolites.ResultsContrary to their typical role as anti-inflammatory agents in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…In addition, the important roles of indole derivatives, indole-3-carbinol, and indole-lactic acid predominately produced by L. reuteri in liver protection have consistently been demonstrated, possibly via antioxidant, anti-inflammatory, and antiapoptotic mechanisms, in agreement with our findings. ,, …”
Section: Discussionsupporting
confidence: 91%
“…In addition, the important roles of indole derivatives, indole-3-carbinol, and indole-lactic acid predominately produced by L. reuteri in liver protection have consistently been demonstrated, possibly via antioxidant, anti-inflammatory, and antiapoptotic mechanisms, in agreement with our findings. ,, …”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have found that TLRs play an important role in inflammation and are closely related to clinical inflammatory diseases 46,47 . The key role of TLRs in liver failure has been studied 48,49 . TLR4 has been reported to be a therapeutic target for prevention and treatment of liver failure 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 The key role of TLRs in liver failure has been studied. 48 , 49 TLR4 has been reported to be a therapeutic target for prevention and treatment of liver failure. 50 , 51 In addition, studies have shown that TLR4 plays a key role in activating innate immunity by directly recognizing LPS.…”
Section: Discussionmentioning
confidence: 99%